Sozophytes in the flora of the Lower Dniper flood-plain (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
In the article, the list of sozophytesof the Lower Dniperflood-plain is given with 38species of vascular plants described. Among them, 23 species grow undoubtedly here (Agropyron dasyanthumLedeb.,Aldrovanda vesiculosaL.,Astrodaucus littoralis(M.Bieb.) Drude,Centaurea brevicepsIljin,Ceratophyllum tanaiticumSapjeg.,Epipactis palustris(L.) Crantz.,Eryngium maritimumL.,Leucojum aestivumL.,Lindernia procumbens(Krock.) Borbs,Nymphaea albaL.,Nymphoides peltata(S.G.Gmel.) O.Kuntze,Orchis palustrisJacq.,Rumex ucrainicusFisch. ex Spreng.,Salvinia natans(L.) All.,Senecio borysthenicus(DC.) Andrz.,Stipa borysthenicaKlokov ex Prokud.,Thymus borysthenicusKlokov et Des.-Shost.,Tragopogon borysthenicusArtemcz.,Trapa natansL. s.l.,Urtica kioviensisRogow.,Utricularia vulgarisL.,Vitis sylvesrisC.C.Gmel.,Zostera marinaL.); 7species has doubtful status (Astragalus borysthenicusKlokov,Carex secalinaWilld. ex Wahlenb.,Cerastium ucrainicumPacz. ex Klokov,Elatine hungaricaMoesz,Goniolimon graminifolium(Aiton) Boiss.,Schoenus nigricansL., Trachomitumvenetumsubsp. sarmatiense(Woodson) V.E.Avet.), 5 species are given erroneously(Achillea ochroleucaEhrh.,Alyssum borzaeanumE.I.Nyjarady,Centaurea paczoskiiKotov ex Klokov,Dianthus bessarabicusKlokov,Suaeda bacciferaPall.), and 3 species only as cultivated (Betula borysthenicaKlokov,Convalaria majalisL.,Quercus roburL.). 30sozophytes, including doubtful, which occupy 60positions in various red lists: World Red List-3 species, European Red List -8, Red Data Book of Ukraine -11, Bern Convention -6, CITES-2, Red List of Kherson area –30 species.
Keywords: sozophytes,Lower Dnieperflood-plain.